10.1016/s1544-8800(08)70400-7 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Prior reports of internal jugular vein (IJV) access for implantation of leadless pacemakers (LLPM) are primarily small series and for ventricular LLPM. OBJECTIVES: To describe outcomes of consecutive patients undergoing IJV access for both atrial and ventricular LLPM implantation. METHODS: This observational multicenter study included 32 consecutive patients (17 female; 69 ± 14 years; range 17-91) undergoing LLPM implantation via IJV access. Dual chamber LLPM was implanted in 16 patients, right ventricular (RV) only in 13, and right atrial (RA) only in 3. Electrical parameters were measured at implantation, 7-10 days post implantation, and at last follow-up (mean 215 ± 98 days). RESULTS: IJV access was successful in all patients. Mean procedure and fluoroscopy times were 82 ± 40 and 16 ± 9 min, respectively. RV implant required 1.3 ± 0.6 deployments with mean of 21 min and RA implant required 1.6 ± 0.9 deployments with mean of 31 min. Electrical parameters were excellent. Current of injury for the RA LLPM is the primary indicator of engagement of the atrial myocardium. Two device-related complications occurred without clinical sequelae; no late complications were observed. Fifteen patients were discharged the same day. CONCLUSIONS: IJV access for atrial and ventricular LLPM implantation is safe and effective across a broad age range and is an alternative to FV access, enabling same-day discharge and early ambulation. Elevated acute atrial capture thresholds with robust current of injury should not prompt repositioning, as thresholds significantly improve at early follow-up.